2021
DOI: 10.5194/nhess-2021-70
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Variable-resolution building exposure modelling for earthquake and tsunami scenario-based risk assessment. An application case in Lima, Peru

Abstract: Abstract. We propose the use of variable resolution boundaries based on Central Voronoi Tessellations (CVT) to spatially aggregate building exposure models for risk assessment to various natural hazards. Such a framework is especially beneficial when the spatial distribution of the considered hazards present intensity measures with contrasting footprints and spatial correlations such as in coastal environments. This proposal avoids the incorrect assumption that a single intensity value from hazards with low sp… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(13 citation statements)
references
References 66 publications
3
10
0
Order By: Relevance
“…The fragility models of Suppasri et al, (2013) predict larger values with respect to the model proposed by De whose functional values were found within the range as if flow velocity was accounted. These findings are in 460 line with the observations of Park et al, (2017);and Song et al, (2017). These studies concluded that flow-depth models predict larger probabilities of complete damage for buildings than models which that addressed tsunami velocity in their derivation.…”
Section: Tsunami Risksupporting
confidence: 88%
“…The fragility models of Suppasri et al, (2013) predict larger values with respect to the model proposed by De whose functional values were found within the range as if flow velocity was accounted. These findings are in 460 line with the observations of Park et al, (2017);and Song et al, (2017). These studies concluded that flow-depth models predict larger probabilities of complete damage for buildings than models which that addressed tsunami velocity in their derivation.…”
Section: Tsunami Risksupporting
confidence: 88%
“…Other methods focused on the exposure component and associated soil properties; this includes manipulating data (i.e., relocation - Bazzurro and Park 2007) or refining data's spatial resolution (i.e., disaggregation -Dabbeek and Silva 2020). More recent spatial representation of exposure suggested using Central Voronoidal Tessellations (CVT) to create exposure models with variable spatial resolutions (Gomez-Zapata et al 2021;Pittore et al 2020). This study will focus mainly on portfolio relocation and disaggregation methods as a way to treat the bias in risk arising from low spatial resolution.…”
mentioning
confidence: 99%
“…For such a purpose, we recommend using variable-resolution exposure models in the form of central Voronoi tessellations (CVTs). Besides spatially representing the building portfolio, they also provide a representative IM per geocell for reliable and computationally efficient vulnerability estimations (Pittore et al, 2020;Gomez-Zapata et al, 2021e). They also implicitly serve as common minimum reference unit (MRU) aggregation entities between exposure and hazard (Zuccaro et al, 2018).…”
Section: Proposed Methodsmentioning
confidence: 99%
“…We use the dataset compiled by Gomez- Zapata et al (2021e), which is composed of six earthquakes with moment magnitudes ranging from 8.5 to 9.0 M w , which were made available in Gomez- . In that dataset, each event is represented by an associated 1000 realisations of crosscorrelated ground motion fields (GMFs) for peak ground acceleration (PGA) and spectral accelerations (S.A.) at 0.3 and 1.0 s. The selection of these spectral periods depends on the fragility function's IM associated with the building classes of the exposure model (Sect.…”
Section: Scenarios Of Earthquakes and Tsunamis For Limamentioning
confidence: 99%
See 1 more Smart Citation